Low‐Dose Aspirin Acetylates Cyclooxygenase‐1 in Human Colorectal Mucosa: Implications for the Chemoprevention of Colorectal Cancer. Issue 1 (4th April 2017) - Patrignani, P; Sacco, A; Sostres, C; Bruno, A; Dovizio, M; Piazuelo, E; Di Francesco, L; Contursi, A; Zucchelli, M; Schiavone, S; Tacconelli, S; Patrono, C; et al.
Abstract : The mechanism of action of low‐dose aspirin in the prevention of colorectal cancer (CRC) remains largely hypothetical. We aimed to compare the effects of low‐dose aspirin (100 mg/day for 7 days) given to 40 individuals undergoing CRC screening on the extent of cyclooxygenase (COX)‐1 acetylation at serine‐529 (AceCOX‐1), in blood platelets vs. colorectal mucosa, at 7 (group 1) and 24 h (group 2) after dosing. A significantly ( P < 0.01) lower %AceCOX‐1 was detected in colonic and rectal mucosa (average 64%) vs. platelets (average 75%) in both groups. This effect was associated with an average 46% ( P < 0.01) and 35% ( P < 0.05) reduction in prostaglandin (PG) E2 levels and phosphorylated S6 (p‐S6) levels, respectively. Rectal mucosal levels of p‐S6/S6 significantly ( P < 0.01) correlated with PGE2 . These findings demonstrate that low‐dose aspirin produces long‐lasting acetylation of COX‐1 and downregulation of p‐S6 in human colorectal mucosa, an effect that may interfere with early colorectal carcinogenesis.